Homo‐ and heteropolymer self‐assembly of recombinant trichocytic keratins. Issue 10 (24th July 2017) - Parker, Rachael N.; Roth, Kristina L.; Kim, Christina; McCord, Jennifer P.; Van Dyke, Mark E.; Grove, Tijana Z.
Abstract: In the past two decades, keratin biomaterials have shown impressive results as scaffolds for tissue engineering, wound healing, and nerve regeneration. In addition to its intrinsic biocompatibility, keratin interacts with specific cell receptors eliciting beneficial biochemical cues. However, during extraction from natural sources, such as hair and wool fibers, natural keratins are subject to extensive processing conditions that lead to formation of unwanted by‐products. Additionally, natural keratins suffer from limited sequence tunability. Recombinant keratin proteins can overcome these drawbacks while maintaining the desired chemical and physical characteristics of natural keratins. Herein, we present the bacterial expression, purification, and solution characterization of human hair keratins K31 and K81. The obligate heterodimerization of the K31/K81 pair that results in formation of intermediate filaments is maintained in the recombinant proteins. Surprisingly, we have for the first time observed new zero‐ and one‐dimensional nanostructures from homooligomerization of K81 and K31, respectively. Further analysis of the self‐assembly mechanism highlights the importance of disulfide crosslinking in keratin self‐assembly. Abstract :